Concurrent true inferoposterior left ventricular aneurysm and ventricular septal rupture secondary to inferior myocardial infarction: a case report. Issue 4 (27th November 2018) - Zhang, Pengfei; Pang, Xinyan; Yu, Dexin; Zhang, Yun
Abstract: Background: Although left ventricular aneurysm (LVA) is the most common mechanical complication of myocardial infarction (MI), it rarely involves the inferior or posterior left ventricular wall. Ventricular septal rupture (VSR) may be a fatal mechanical complication of MI but rarely occurs in the posterior or inferior portion of the interventricular septum. Thus, LVA and VSR as two mechanical complications of MI in the same patient are extremely rare. Case summary: A 65-year-old woman, who had inferior ST-segment elevation myocardial infarction 2 months before without reperfusion therapy, was admitted with exertional dyspnoea for 1 month. Echocardiography and computed tomography revealed true inferoposterior LVA and VSR as concurrent complications of MI. These imaging findings were confirmed during cardiac surgery. After successful coronary bypass grafting and ventriculoplasty, the patient recovered quickly and was discharged from the hospital. Discussion: A rare case of post-infarction inferoposterior LVA with concurrent interventricular septal rupture was reported. Transthoracic and transoesophageal echocardiography and cardiac computed tomography were valuable tools for the diagnosis of this rare condition. Combined coronary bypass grafting and ventriculoplasty were effective in treating this often fatal complication of inferior MI.